2015
DOI: 10.1037/sgd0000091
|View full text |Cite
|
Sign up to set email alerts
|

Distinct coping combinations are associated with depression and support service utilization in men who have sex with men living with HIV.

Abstract: Stigma and stress may place HIV-positive men who have sex with men (HIV+ MSM) at risk for depression. Additionally, HIV+ MSM might utilize multiple HIV-related services as a way to gain support for, and more effectively manage, HIV-related stressors. Although prior research has demonstrated that depression severity and utilizing support services are associated with functional or dysfunctional coping strategies, researchers have not investigated the impact of different coping combinations—specifically, the conc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 67 publications
2
12
0
Order By: Relevance
“…Based on our findings, dysfunctional coping strategies appear to have a greater individual effect on levels of depressive symptoms and suicidality for TGNC individuals than the presence of functional coping strategies alone. This is a finding that has been previously reported using a sexual minority sample (Rood et al., ). It may be that this finding holds true across sexual and gender minority samples and, thus, should be investigated further.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Based on our findings, dysfunctional coping strategies appear to have a greater individual effect on levels of depressive symptoms and suicidality for TGNC individuals than the presence of functional coping strategies alone. This is a finding that has been previously reported using a sexual minority sample (Rood et al., ). It may be that this finding holds true across sexual and gender minority samples and, thus, should be investigated further.…”
Section: Discussionsupporting
confidence: 85%
“…The proportional odds model estimated the odds of being in a less severe depression category, with the HFLD, the hypothesized "optimal" coping profile, as the reference group. This choice reflects findings from the extant literature, which has shown that the frequent use of functional coping strategies, in comparison to dysfunctional strategies, are more commonly associated with favorable health outcomes (e.g., Rood, McConnell, & Pantalone, 2015). Next, we tested for an association between the coping profiles and suicidality prior to transition/gender affirmation by fitting a logistic regression model, adjusting for sociodemographic factors.…”
Section: Discussionmentioning
confidence: 99%
“…Doing so embraces the inherent knowledge and skills within an individual and suggests that these traditionally marginalized communities have, in spite of facing multiple adversities, developed resilient responses to these experiences. 60 Our results also showed two coping strategies (i.e., spirituality and positive reframing) seemed to emerge more strongly in response to inter-group discrimination experiences. Of note, these strategies aim to change one's own outlook or interpretation rather than to bring about a change in the external circumstances of the situation.…”
Section: Discussionsupporting
confidence: 56%
“…Prior research and guidance suggest that the factor structure of the Brief COPE depends on the context and population being studied and, thus, researchers have used exploratory factor analysis to identify subscales for their specific sample (Carver, 1997; Krägeloh, 2011; Rood, McConnell, & Pantalone, 2015). In our study, we conducted an exploratory factor analysis using varimax rotation and extracted eight factors with an eigenvalue >1 (Comrey & Lee, 2013; Kaiser, 1960).…”
Section: Methodsmentioning
confidence: 99%